Analysis of an Infectious Diseases Pharmacist on Call Pager Program to Inform Educational Efforts. (August 2017) - Gilbert, Elise M.; Rhodes, Nathaniel J.; McLaughlin, Milena M.; Cottreau, Jessica M.; Scheetz, Marc H.; Postelnick, Michael; Barr, Viktorija O.
Background: An on call infectious diseases (ID) pharmacist may be used as a resource for physicians, pharmacists, and other health care providers to help answer questions regarding anti-infective agents.Objective: To assess type, requestor, resources dedicated, and temporal trends of questions received through an ID pharmacist on call pager program. A secondary objective was to gather insight as to how this information was utilized to inform educational initiatives.Methods: This was a retrospective study of questions received by the ID pharmacist on call via pager at a large academic medical center. Question data were documented in a central database and analyzed to assess temporal trends and question type, and qualitatively analyzed to determine areas for targeted educational efforts.Results: The ID pharmacist on call recorded 545 questions during the 1-year study period; questions were composed of various antimicrobial agent–related queries, including antibiotic spectrum and selection (n = 251, 46.1%), dosing of antimicrobials (n = 195, 35.8%), and drug monitoring (n = 26, 4.8%). Targeted educational initiatives secondary to questions received included pharmacist education regarding the use of polymyxin antibiotics and antibiotic dosing protocol updates.Conclusions: An ID pharmacist on call pager program was utilized to inquire about antibiotic spectrum and selection for the majority of questions. Records of questions received may be utilized to direct educational efforts and create or revise targeted resources for pharmacists and other clinicians.